The analysis reveals novel hub genes and pathways associated with Tetralogy of Fallot - Wen, Heling; Huang, Zheng; Mao, Yujie; Tian, Wenjie; Peng, Lei; Chen, Yu (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTetralogy of Fallot (TOF) is one of the most common complex congenital heart diseases, posing a severe threat to infant health. This study aims to investigate the core genes and pathways associated with TOF to identify potential targets for prevention and intervention. This study aims to explore the core genes and pathways associated with TOF, providing a reference for identifying potential targets for the prevention and intervention of this disease.MethodsBulk and single-cell RNA-seq datasets were employed in this study. Differentially expressed genes (DEGs) were calculated, and functional enrichment analysis was performed. The expression of the hub genes was validated by quantitative real-time polymerase chain reaction (qRT-PCR). The dysregulated genes and pathways were further validated at the single-cell resolution.ResultsThe DEGs analyzed from two datasets, GSE146220 and GSE217772, were subjected to intersection analysis, resulting in 29 consistently upregulated genes (UpGs) and 22 consistently downregulated genes (DpGs). The qRT-PCR analysis confirmed that the expression of upregulated and downregulated genes was generally consistent with the results of the bioinformatics analysis. Functional enrichment analysis based on four distinct databases has shown that fatty-acid beta-oxidation and related pathways were consistently enriched. With snRNA-seq data, we found that the UpGs were enriched in cardiomyocytes, and the DpGs were enriched in cardiofibroblasts. Meanwhile, it was shown that the TOF tissue had a higher ssGSEA score for fatty acid metabolism-associated pathways. Notably, these fatty acid metabolism pathways were mostly enriched in cardiomyocytes.ConclusionThis study identified that TOF DEGs are highly enriched in fatty-acid beta-oxidation and related pathways. The snRNA-seq data of TOF showed that fatty acid metabolism pathways are predominantly enriched in cardiomyocytes. These findings contribute to further understanding the potential pathogenic mechanisms of TOF and identifying potential therapeutic targets.